Exploring the Influence of Out-of-Specialized-Field Teaching on Educators Development and Motivation - Obias, Dianne C.; Matitu, Chris Aida B.; Almodovar, Bianca Jade; Nacu, Kelly Francine C.; Orsua, Romelie D.; Carlos, Julius L.; Simon, Christian Louie C. (Future Science / FSH-PH Publications, 2025)
Teaching outside your field of expertise means handling a subject you are not trained in or familiar with. This study presents the experiences of teachers assigned to teach subjects outside their area of specialization, focusing on their motivation and development. The study explores the impact of teaching outside their specialization on a teacher's development and motivation. Through a qualitative phenomenology approach, in-depth interviews were conducted with preselected Senior High school teachers in a private educational institution located in Guagua, Pampanga, the Philippines, teaching subjects that are not their field of expertise and fit the researcher’s established criteria. The complexity of teaching outside one’s specialization and how educators adapt to these demands. The study uncovers opportunities for professional growth. For some, the experience fostered resilience and broadened their perspectives, enabling them to become more versatile educators. Positive student responses give them a sense of fulfillment despite all the challenges. According to results, out-of-specialized-field teaching presents new challenges, but it helps show their adaptability, and resourcefulness and unlock more creative teaching strategies with the purpose of providing quality education. By focusing on the lived experiences of teachers, teachers should recognize teaching outside their specialization as a valuable opportunity for personal and professional growth, promoting a growth mindset that encourages embracing challenges.